Peningkatan keterampilan membaca pemahaman menggunakan model pembelajaran scramble wacana pada siswa kelas IV sekolah dasar - Lasma Rohani Elisabeth; Rukayah Rukayah; Tri Budiharto (Didaktika Dwija Indria, 2020)
The purpose of this research is to improve reading comprehension skills through scramble learning models for grade IV students of primary schools. in this study the subjects studied were grade IV students of SD Negeri Mangkubumen Kulon No. 83 Surakarta in the 2019/2020 school year with a total of 16 students. In this research, researchers used several techniques in data collection, namely the activity of tests, interviews and observation. Data analysis of content validity and data triangulation. The analysis data techniques used are interactive analysis model of Miles-Huberman techniques. From the research on the application of the scramble learning model during the two cycle research, the following results were obtained, in the first cycle the classical completeness was 37.50%, then in the second cycle it was 100%. based on these results it can be concluded that the students' reading comprehension skills have increased from the pre-action stage,  first cycle and second cycle. As for the contribution  this study, teachers can use the scramble learning model in reading comprehension learning activities.